MATHEMATICAL MODELS IN BUSINESS ACCOUNTING. - Mattessich, Richard (The Accounting Review, 1958)
This paper draws attention to the increasing use of the concept of "model" in accounting literature. It distinguishes between economic models and accounting models, defines the latter, demonstrates the presentation of a whole accounting cycle in the mathematically formal way of an accounting model, discusses by way of a practical example the independent and dependent variables in such a system and shows how the structure of accounting models is graphically presentable. It finally gives, with the aid of some balance-sheet-ratios, an example of combining accounting models with economic models and indicates the application of this approach to a prospective area which still can be considered to be the accountant's. The paper, however, intends to be nothing more than an experiment. There is no denial that the conscious and systematic application of mathematical models to certain branches of economic science opened new paths and perspectives, not without enriching our insight into many a problem. It therefore seems to be comprehensible if accountants try to dabble and experiment in this apparently promising field.